Effect of Night-Clinic Closure on Physicians’ Workload and Satisfaction - Zhang Chunyu; Liu Yuanli (Journal of Preventive Medicine And Care, 2018)
Excessive overtime work, which is a serious problem among Chinese physicians, is the primary reason for night clinic closure policies. The aim of this study was to evaluate the effects of such policies on physicians’ workload and satisfaction. Physicians at the hospital, which closed its night clinic in 2017, were selected as the intervention group, and those at another hospital, which still operates a night clinic, were chosen as the control group. In total, 829 participating physicians self-reported their characteristics and responded to questions on three effect indicators: weekly hours worked, work–family balance, and job satisfaction; the index years were for 2016 and 2017. A pre–post-with-control-group study design and the difference-in-difference (DID) methodology were employed to evaluate the effect of night clinic closure. After adjusting for physicians’ characteristics, the effect of all variables, except hours worked per week, on work–family balance and job satisfaction remained significant. Although the adjusted effect on hours worked per week was not significant, our results suggest that minor policy changes that reduce the workload of physicians may nonetheless benefit this group. However, as the satisfaction scores remained low, other policies should be implemented to relieve the workload and improve satisfaction among physicians.
Keywords: Night-clinic closure